If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(5s + -4) + -8 = -2(7s + 7) + -2 Reorder the terms: -2(-4 + 5s) + -8 = -2(7s + 7) + -2 (-4 * -2 + 5s * -2) + -8 = -2(7s + 7) + -2 (8 + -10s) + -8 = -2(7s + 7) + -2 Reorder the terms: 8 + -8 + -10s = -2(7s + 7) + -2 Combine like terms: 8 + -8 = 0 0 + -10s = -2(7s + 7) + -2 -10s = -2(7s + 7) + -2 Reorder the terms: -10s = -2(7 + 7s) + -2 -10s = (7 * -2 + 7s * -2) + -2 -10s = (-14 + -14s) + -2 Reorder the terms: -10s = -14 + -2 + -14s Combine like terms: -14 + -2 = -16 -10s = -16 + -14s Solving -10s = -16 + -14s Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '14s' to each side of the equation. -10s + 14s = -16 + -14s + 14s Combine like terms: -10s + 14s = 4s 4s = -16 + -14s + 14s Combine like terms: -14s + 14s = 0 4s = -16 + 0 4s = -16 Divide each side by '4'. s = -4 Simplifying s = -4
| 8(3x-5)=10x+2 | | 1.9=w+0.42 | | 2x+4=5x-14 | | 3(5x-3)-8(x-1)= | | 3+x=2 | | 6*x^2-2*x=0 | | 8m=24 | | x^2+4x+xz= | | 13x-2(6x-4)=72 | | -5x-3=-10x-7 | | 3(3x-3)=9(x-1) | | 7m=4m+21 | | 7y+64=-13 | | -10x+7=-5x+3 | | 4(k-3)+7=2k-(k+8) | | -3k-2=-44 | | -3x+3(13+5x)=3 | | 16-2x-7-2=4x+7 | | -14r=49 | | 27-5x=-7 | | 11x^2-31x-10=0 | | 5(I-4)=4-3k | | 3+6=9+32 | | 7x^2+84=0 | | 3+x=9+32 | | x+2x=165 | | 42=-7(j-4) | | -10x-7=-5x-3 | | Y-21=-12 | | 7x-9=6x-2 | | 4x-11(2x-3)+15(x+7)= | | 2x^2-42x=-40 |